Harrodian instability in Kaleckian models and Steindlian solutions - Eckhard Hein (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2019)
The notion of dynamic instability of demand driven growth put forward by Harrod (1939) has triggered several responses in the history of economic thought. The modern Kaleckian solution, including Bhaduri/Marglin (1990) among several others, considers the rate of capacity utilisation to be endogenous beyond the short run, thus assuming, explicitly or implicitly, that Harrod's warranted rate of growth is either irrelevant or endogenous in the long run, eliminating the problem of Harrodian instability. In the modern debate several authors have criticised this Kaleckian approach, as reviewed in Hein/Lavoie/van Treeck (2011, 2012). In this debate, however, two arguments proposed by Steindl (1979, 1985) in favour of at least partial endogeneity of the warranted rate of growth have received little attention. The first is related to the endogeneity of the capital output ratio through endogenous capital scrapping (Steindl 1979); the second refers to government budget balances and the related effects on the aggregate propensity to save (Steindl 1979, 1985). In this paper we will therefore discuss in particular the two Steindlian arguments. For this purpose the model framework proposed by Hein/Lavoie/van Treeck (2011, 2012) will be extended in order to allow for endogenous capital scrapping and endogenous overall propensities to save through variations in the government financial balance.
Keywords: E12; E20; O41; 330; Kaleckian distribution and growth models; Harrodian instability; Steindl